2016
DOI: 10.1016/j.memsci.2016.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancement of mechanical properties and CO2 selectivity of ZIF-8 mixed matrix membranes: Interfacial toughening effect of ionic liquid

Abstract: Fine-tuning of interfacial adhesion between fillers and polymer matrices is crucial to the separation performance of mixed matrix membranes (MMMs) and their mechanical properties.Direct incorporation of metal organic framework (MOF) particles in polymers often leads to insufficient adhesion and non-selective interfacial voids. Herein, we present a novel strategy to develop toughened MOF-polymer interface by confining a room temperature ionic liquid (IL)[bmim][Tf 2 N] into ZIF-8 cages. The diffusion of the IL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(129 citation statements)
references
References 46 publications
14
114
1
Order By: Relevance
“…[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] In this method, ILs are first dissolved in an excess amount of an inert solvent, such as acetone, methanol, or ethanol, to provideb etter dispersion.…”
Section: Wet Impregnation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] In this method, ILs are first dissolved in an excess amount of an inert solvent, such as acetone, methanol, or ethanol, to provideb etter dispersion.…”
Section: Wet Impregnation Methodsmentioning
confidence: 99%
“…Li et al [55] showedt hat the interfacial adhesion between MOF and polymer can be improved by impregnating ILs into the MOF cages. However,t here is another important issue related to MMMs, which is the adhesionp roblems that may occur betweenM OFs and polymers.…”
Section: The [C 3 Nh 2 Bim][tf 2 N]/nh 2 -Mil-101(cr)/pim-1 Membrane mentioning
confidence: 99%
“…[8][9] IL-MOF combinations have been considered recently in the gas separation field. [10][11][12][13][14][15][16] For instance, Chen et al 17 incorporated IRMOF-1 composite and reported a CO 2 /N 2 selectivity of 70 at ambient conditions. To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the hypothesis that the ILs embedded in the outer surface of MOF fillers could act as sealants between the filler and polymer phases, Li and co-workers [157] proposed to incorporate ILs in MOFs instead of dispersing free ILs and MOFs directly in polymer matrix. IL@ZIF-8 fillers were prepared by soaking activated ZIF-8 in [bmim][Tf 2 N]/methanol solution.…”
Section: Mixed Matrix Membranes (Mmms)mentioning
confidence: 99%